The Relationship of Happiness and Quality of Educational Services with Academic Burnout Among Students of Zahedan University of Medical Sciences, Iran - Azizollah Arbabisarjou; Omolbanin Rahdar; Somayeh Shahroudi (Kerman University of Medical Sciences, 2019)
Background Paying attention to students' academic burnout and identifying the factors affecting it is one of the concerns of higher education authorities. Objectives The purpose of this study was to investigate the effect of quality of educational services and happiness on students' academic burnout. Methods In this descriptive-analytical study, 477 students of Zahedan University of Medical Sciences participated in the academic year 2017 - 2018. The sampling method was stratified. Data were collected using the SERVQUAL Questionnaire, Isfahan-Fordyce Happiness Inventory (IFHI) and Breso Burnout Questionnaire. Then, they were analyzed by Pearson's correlation coefficient, independent -test, One-way ANOVA and Multiple linear regression using SPSS. P value less than 0.05 was considered significant. Results According to Pearson correlation coefficient, there was a significant relationship between students' happiness and academic burnout (P < 0.001), but there was no significant relationship between the quality of educational services and academic burnout (P = 0.060). The level of academic burnout was higher in male students than in female students (P = 0.003). Multiple linear regression analysis showed that only the students' happiness variable significantly predicted variations in academic burnout (P = 0.001). Conclusions In order to reduce students' academic burnout, effective factors such as happiness should be considered by the respective authorities and educational packages should be used to promote happiness and increase the quality of educational services.